Oxygenation index and NT-proBNP as predictors of pulmonary hypertension and ventilation/perfusion mismatch in acute pulmonary embolism - Ye, Wenjing; Chen, Xi; Li, Xiaoming; Guo, Xuejun; Gu, Wen (Frontiers in Cardiovascular Medicine, 2023)
Introduction The magnitude of pulmonary artery pressure (PAP) and the extent of ventilation/perfusion (V/Q) mismatch are essential for assessing the prognosis of acute pulmonary embolism (APE). We aimed to develop a model for predicting the status of the pulmonary circulation and arterial gas exchange functions using serum levels of cardiac biomarkers and arterial oxygenation index (OI) values. Materials and methods This single-center, retrospective observational cohort study included 224 patients with APE. Multivariate linear regression and Poisson regression were used to test the statistical association between cardiac biomarkers, OI, PAP, and V/Q mismatch. Diagnostic efficiency was calculated from a receiver operating characteristic (ROC) curve. Results Serum levels of troponin I (TNI), N-terminal pro-brain natriuretic peptide (NT-proBNP), and arterial OI magnitude significantly correlated with PAP and V/Q mismatches (P < 0.05). Multivariate linear regression showed that NT-proBNP serum levels (β = 0.002, P < 0.001) and OI values (β = −0.022, P = 0.001) significantly influenced PAP. Arterial OI (β = −0.039, P < 0.001) had a significant influence on the percentage of pulmonary vascular obstruction (PVO) as determined by perfusion scanning. Poisson regression showed that OI (odds ratio: 0.995, p < 0.001) was a predictor of the number of lung segments with V/Q mismatches. ROC area under the curve (AUC) values of NT-proBNP and OI predicting pulmonary hypertension were 0.716 and 0.730, respectively, and for V/Q mismatch scanning, the results were 0.601 and 0.634, respectively. Conclusion Arterial OI and serum levels of cardiac biomarkers may be used as indicators of pulmonary hypertension and V/Q mismatch.